Hegel e la questione femminile al crocevia con il diritto - Magni, Chiara (B@belonline, 2024)
It is well known that in §§ 165-166 of the Grundlinien, as well as in his Lectures, Hegel, in line with the sensibilities of the time, expresses himself in favour of the gender roles. This contribution, through a comparison of two of the main codes of the time, the Allgemeines Landrecht für die Preußischen Staaten (1794) and the Code Civil (1804), attempts to reconstruct some aspects of the legal context of the late 18th/early 19th century and, in particular, of family law – the main and decisive source of law for understanding the gender structure in modern, bourgeois society. This should allow us, on the one hand, to illuminate Hegel’s partial modernity with regard to women’s rights and, on the other, to understand the extent to which he can be justified as a ‘child of his time’ with regard to his judgements on women.